Polimorfisme gen COL1A1 sebagai faktor risiko terjadinya prolaps organ panggul pada perempuan Bali, Indonesia - Putra Agung Eka Aricandana; I Gede Mega Putra; I Wayan Megadhana; Anak Agung Ngurah Anantasika; Ida Bagus Gde Fajar Manuaba; I Gede Ngurah Harry Wijaya Surya (Intisari Sains Medis, 2022)
Introduction: Pelvic organ prolapse (POP) is still a common health problem in women, especially in the elderly female population. Pelvic organ prolapse is associated with a reduced quality of life for millions of women worldwide. The purpose of this study was to determine the role of the COL1A1 rs 1800012 gene polymorphism as a risk factor for pelvic organ prolapse in Balinese women, Indonesia.Methods: This case-control observational study involved 60 Balinese women aged 30-70 years divided into 30 subjects with pelvic organ prolapse as a case group and 30 subjects with non-pelvic organ prolapse as a control group. Subject selection and clinical examination were carried out at the Reconstructive Urogynecology Polyclinic and Obstetrics and Gynecology Polyclinic, Sanglah Central General Hospital Denpasar and Prima Medika General Hospital Denpasar. Three ml of blood sample was drawn and then put into a bottle containing EDTA for Polymerase Chain Reaction COL1A1 rs 180012 gene polymorphisms at the Integrated Biomedical Laboratory, Faculty of Medicine, Udayana University. The data obtained were then analyzed using the Statistical Product and Service Solutions software version 21.0.Results: COL1A1 gene polymorphism was found in eight subjects in the case group and one subject in the control group. The results of bivariate analysis showed a significant relationship between the COL1A1 gene polymorphism and the incidence of pelvic organ prolapse (p = 0.011). The results of multivariate analysis revealed a significant relationship between COL1A1 gene polymorphisms and pelvic organ prolapse after controlling for controlled variables (parity status, occupation, BMI, age, menopause, and history of hysterectomy). Multivariate analysis showed adjusted odd ratio of 16.157 for the COL1A1 gene polymorphism (p = 0.021).Conclusion: COL1A1 gene polymorphism significantly increases the risk of pelvic organ prolapse in Balinese women.  Pendahuluan: Prolaps organ panggul (POP) masih menjadi masalah kesehatan umum pada perempuan, terutama pada populasi wanita lanjut usia. Prolaps organ panggul berkaitan dengan penurunan kualitas hidup dari jutaan wanita di seluruh dunia. Tujuan dari penelitian ini adalah untuk mengetahui peran polimorfisme gen COL1A1 rs 1800012 sebagai faktor risiko kejadian prolaps organ panggul pada perempuan Bali, Indonesia.Metode: Studi observasional kasus kontrol ini melibatkan 60 orang perempuan Bali berusia 30-70 tahun yang terdiri dari 30 orang dengan diagnosis prolaps organ panggul sebagai kelompok kasus dan 30 orang dengan diagnosis non prolaps organ panggul sebagai kelompok kontrol. Pemilihan subjek dan pemeriksaan klinis dilakukan di Poliklinik Uroginekologi Rekonstruksi dan Poliklinik Obstetri dan Ginekologi Rumah Sakit Umum Pusat Sanglah Denpasar dan Rumah Sakit Umum Prima Medika Denpasar. Sampel darah diambil sebanyak 3 ml kemudian dimasukkan ke dalam botol yang berisi EDTA dan dilakukan pemeriksaan Polymerase Chain Reaction untuk polimorfisme gen COL1A1 rs 180012 di Laboratorium Biomedik Terpadu Fakultas Kedokteran Universitas Udayana. Data yang diperoleh kemudian dianalisis menggunakan perangkat lunak Statistical Product and Service Solutions versi 21.0.Hasil: Polimorfisme gen COL1A1 ditemukan pada 8 subjek pada kelompok kasus dan 1 subjek pada kelompok kontrol. Hasil analisis bivariat menunjukkan adanya hubungan signifikan antara polimorfisme gen COL1A1 dan kejadian prolaps organ panggul (p = 0,011). Hasil analisis multivariat memperjelas hubungan signifikan antara polimorfisme gen COL1A1 dan prolaps organ panggul setelah dikontrol dengan variabel terkendali (status paritas, pekerjaan, imt, umur, menopause, dan riwayat histerektomi). Hasil analisis multivariat menunjukkan adjusted odd ratio sebesar 16,157 untuk polimorfisme gen COL1A1 (p = 0,021).Simpulan: Polimorfisme gen COL1A1 secara signifikan meningkatkan risiko terjadinya prolaps organ panggul pada perempuan Bali.